2022
DOI: 10.1523/jneurosci.0350-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Stretch Gates NMDA Receptors

Abstract: Membrane stretch gates NMDA receptor currents in the absence of neurotransmitter. Stretchgated currents have the biophysical hallmarks of the glutamate-gated currents including requirement for glycine, large Na + conductance, high Ca 2+ permeability, and voltage-dependent Mg 2+ block..

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“… 58 A recent study has demonstrated that stretching plasma membrane can mechanically activate NMDAR independent of glutamate. 59 By counteracting swelling, active shrinkage prevents membrane stretching; thus, it may block a potential mechanically induced excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“… 58 A recent study has demonstrated that stretching plasma membrane can mechanically activate NMDAR independent of glutamate. 59 By counteracting swelling, active shrinkage prevents membrane stretching; thus, it may block a potential mechanically induced excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies have confirmed that NMDAR is mechanically sensitive (Casado and Ascher, 1998 ; Belin et al, 2022 ). In the model of stretch-induced neuronal injury, the Mg 2+ blockage of the NMDAR channel significantly decreased and the NMDAR current increased (Zhang et al, 1996 ).…”
Section: Characteristics Of Nmdarsmentioning
confidence: 94%
“…Mechanosensitivity of NMDA receptors (an alternative opening to conventional glutamate induced activation) attracted growing interest recently [ 47 , 102 ]. In our search, among the two studies connecting NMDA receptors to migraine mechanical symptoms, one paper suggests that sec-butylpropylacetamide (SPD), a valproic acid derivative currently in use for migraine prophylaxis, is responsible for enhancing GABAergic transmission while reducing NMDA-mediated currents in cortical neurons [ 103 ].…”
Section: Methodsmentioning
confidence: 99%